2015
DOI: 10.1186/s13058-015-0596-x
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk variants associated with in situ breast cancer

Abstract: IntroductionBreast cancer in situ (BCIS) diagnoses, a precursor lesion for invasive breast cancer, comprise about 20 % of all breast cancers (BC) in countries with screening programs. Family history of BC is considered one of the strongest risk factors for BCIS.MethodsTo evaluate the association of BC susceptibility loci with BCIS risk, we genotyped 39 single nucleotide polymorphisms (SNPs), associated with risk of invasive BC, in 1317 BCIS cases, 10,645 invasive BC cases, and 14,006 healthy controls in the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 47 publications
(35 reference statements)
1
24
0
Order By: Relevance
“…One study identified a new breast cancer locus for breast cancer at 6q14 (rs17530068) by meta‐analysis of ER‐negative disease and found that rs17530068 was a susceptibility locus for breast cancer in women of European descent . It remains controversial subject as to whether this locus is also a susceptibility locus in Chinese population . Rs4784227 is a site of the cancer susceptibility candidate gene 16 ( CASC16 ).…”
Section: Introductionmentioning
confidence: 99%
“…One study identified a new breast cancer locus for breast cancer at 6q14 (rs17530068) by meta‐analysis of ER‐negative disease and found that rs17530068 was a susceptibility locus for breast cancer in women of European descent . It remains controversial subject as to whether this locus is also a susceptibility locus in Chinese population . Rs4784227 is a site of the cancer susceptibility candidate gene 16 ( CASC16 ).…”
Section: Introductionmentioning
confidence: 99%
“…The 9p21.3 locus in general, and the CDKN2A/CDKN2B genes in specific, are a classic examples of pleiotropic regions since they are associated with a very large number of human traits and diseases171819222324. Pleiotropic regions are probably more accessible DNA stretches than normal and therefore variability within them may result to be non neutral more likely than in any other randomly selected DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…Genetic polymorphisms in the locus have been reported to be associated with type two diabetes mellitus (T2DM), which is a one of the few suggested risk factors for PNETs141516, suggesting a shared genetic background between T2DM and PNETs. Genetic variants belonging to the CDKN2A/2B region have been identified through GWAS as susceptibility markers for several human traits and diseases, including a large number of tumor types1718192021222324. In addition we have recently showed the association of the CDKN2A/2B -rs3217992 SNP with increased risk of pancreatic ductal adenoma carcinoma (PDAC)25.…”
mentioning
confidence: 99%
“…Around 20% of all diagnosed breast tumors are non‐invasive, and the most common in situ histological subtype, ductal carcinoma in situ (DCIS) corresponds to roughly 80% of BCIS diagnoses in the US . While BCIS and invasive BC share epidemiological and, in part also genetic risk factors; it is important to identify any disease specific genetic risk factors, since only a fraction of existing BCIS tumors will progress to the invasive stage …”
mentioning
confidence: 99%
“…Even though a growing number of common, low‐penetrance susceptibility loci for invasive BC are being identified, comparatively few attempts to detect single nucleotide polymorphisms (SNPs) that are specific for breast carcinoma in situ (BCIS) have been made so far and of these several were underpowered . A previous study conducted within the Million Women Study identified 2p‐rs4666451 as being more strongly associated with BCIS risk than with invasive disease .…”
mentioning
confidence: 99%